Les risques naturels dans le gouvernorat d'Assouan (Égypte) : le rôle du Haut Barrage - Mohamed Al Amrawy; Jean-Louis Ballais (Physio-Géo)
This research is an attempt to study natural hazards and their effects on the human occupation in the governorate of Aswan in Egypt. The main natural hazards are due to building of Aswan High Dam: seismic hazard, the most dangerous, linked to Nasser Lake, and flood hazard around Nasser lake that must have disappeared because of stocking of Nil waters and moving windblown sands on the western bank of the river at the expense of an Aswan outlying district. Flood risk has disappeared downstream but rare blocks collapses still threaten a lot of people on the eastern bank of the Nile.